2009
DOI: 10.1017/s0266466609990272
|View full text |Cite
|
Sign up to set email alerts
|

Robust Inference in Autoregressions With Multiple Outliers

Abstract: We consider robust methods for estimation and unit root [UR] testing in autoregressions with infrequent outliers whose number, size and location can be random and unknown. We show that in this setting standard inference based on OLS estimation of an augumented Dickey-Fuller [ADF] regression may not be reliable, since (i) clusters of outliers may lead to inconsistent estimation of the autoregressive parameters, and (ii) large outliers induce a jump component in the asymptotic null distribution of UR test stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This is not surprising since true additive outliers render QML biased (see Mendes [18], Muler and Yohai [47], cf. Cavaliere and Georgiev [13], Muler et al [46]).…”
Section: Assumption 3 (Response Bounds)mentioning
confidence: 97%
“…This is not surprising since true additive outliers render QML biased (see Mendes [18], Muler and Yohai [47], cf. Cavaliere and Georgiev [13], Muler et al [46]).…”
Section: Assumption 3 (Response Bounds)mentioning
confidence: 97%
“…Their set up covers both autoregressions with a unit (or local-to-unit) root and stationary autoregressions, and large-sample properties are obtained under the assumption of …nite fourth moments of the innovations. Near-UR autoregressions augmented with dummy variables have also been analysed in Cavaliere and Georgiev (2009), where it is shown that when …nite-variance innovations are contaminated by infrequent, large outliers, the inclusion of dummy variables increases the e¢ ciency of the AR parameter estimator (leaving the consistency rate unchanged) and gives rise to UR tests with signi…cant power gains.…”
Section: (12)mentioning
confidence: 99%
“…. , Γ l is affected; see Cavaliere and Georgiev (2009) for a univariate result. Our estimators are still consistent in this case, and Gaussian asymptotic inference applies.…”
Section: Remark 24mentioning
confidence: 99%